From Bail to Jail: The Effect of Jail Capacity on Bail Decisions - Williams, Marian Rebecca (American journal of criminal justice, 2016)
One of the more important decisions made by judges in the criminal justice system is the bail decision. Factors that judges take into consideration when making a bail decision, such as seriousness of the offense, flight risk, and public safety, are typically seen by researchers as the primary determinants of such a decision. However, one aspect that researchers have not studied extensively—rated jail capacity – could play an important role in a judge’s decision. Overcrowding in jails leads to numerous problems, both for the offender and the system itself, so judges may be more willing to release offenders into the community during the pretrial period if the local jails are overcrowded. The current study examines the effect of rated jail capacity on decisions regarding bail amounts, release on recognizance (ROR), financial release, and conditional release in eight Florida counties. Results indicate that rated jail capacity plays a role in judges’ bail decisions, suggesting that judges are concerned about housing more pretrial offenders in crowded jails.